Phytomedicine for Controlling Urolithiatic Agents - A. Bimolini Devi2, N. Rajen Singh2; S. Rajendra Singh3, Reena Laikangbam1, M. Damayanti Devi1* (Journal of Experimental Sciences, 2010)
ABSTRACT: Crystal aggregation and retention are critical events in the formation of kidney stones. Traditional plants are a valuable source of novel antibacterials and urine decrystallization agents that are associated with prevention and control of urolithiasis. Urine decrystallization and in vitro antibacterial activity of seventeen plant extracts were assessed. In vitro preparation of synthetic struvite and changes in the final weight of the stone were also determined after treatment with different ethanol extracts of the plants. Aqueous extracts of dried plant samples were used to determine their capacity to control crystallization of urine. Antibacterial susceptibilities were also determined by standard filter-disc diffusion technique. Two known antibiotics were used as positive control. Out of the seventeen plants analysed, Cissus adnata Roxb., Cuminum cyminum L., Eupatorium birmanicum DC., Hibiscus sabdariffa L., Oxalis corniculata L., Piper longum L. and Tamarindus indica L. significantly prevented crystal formation in urine and exhibited strong antibacterial activity against four urolithiasis inducing flora. Ethanol extracts of H. sabdariffa L., T. indica L. and P. longum L. showed comparatively the highest efficacies in dissolving the stone. Thus, C. adnata, C. cyminum, E. birmanicum, H. sabdariffa, O. corniculata, P. longum and T. indica showed promising role in prevention and control of urolithiasis.